Abdullah ka khawab (Children Publication Lahore, 2003)
"Abdullah Ka Khawab" is a magical tale about a young boy's dream. This story encourages children to dream big and believe in the power of their imagination. It explores the themes of hope, perseverance, and the pursuit of one's dreams.